NPID Double Hyperbolic Controller For Improving Tracking Performance Of XY Table Ballscrew Drive System - Che Ku Junoh, Sahida (2019)
Higher tracking accuracy, robustness and disturbance rejection are the three most important elements that are highly demanded to be applied and achieved in the process of controller design in manufacturing process. In this new era where technology keeps rising, controller design for machine tools has caught the attention of most researchers nowadays. However, disturbances such as friction force and cutting force affect the tracking performance of the machine tool. Issues related to cutting force effect on machining have been studied extensively by previous researchers in which different controller techniques are designed to overcome this issue. The conventional controller such as a proportional-integral-derivative (PID) controller is proved to be inadequate in enhancing the tracking performance of the machine tool under the presence of cutting force. Consequently, PID structure is modified by cascading a nonlinear component and PID controller which is named as nonlinear proportional-integral-derivative (NPID) controller. However, an NPID controller also has limitation with respect to the range of stability of the nonlinear gain. Owing to this reason, NPID controller with more than one nonlinear components are proposed to address the issue. Thus, this thesis proposes an NPID Double Hyperbolic controller for improving the tracking performance of the machine tool application. First, the transfer function of the model is obtained via system identification approach which is known as black box approach. Then, the proposed controller is designed. It consists of two embedded hyperbolic nonlinear components known as the nonlinear proportional and the nonlinear integral which are located before the proportional and integral gains, respectively. This controller is validated via simulation and experimental works. The performance of this proposed controller is compared with the two conventional controllers; the PID and the NPID controllers to verify the effectiveness of the proposed controller. This thesis has successfully demonstrated that by adding additional nonlinear hyperbolic components, the tracking performance of a machine tool can increase significantly. The results showed that NPID Double Hyperbolic controller provide an improvement of 94.43% in terms of root mean square error (RMSE) performance and an enhancement of 62.59% in terms of fast fourier transform (FFT) error performance compared to the conventional NPID controller. However, further studies and improvement are needed to study the machine tool performance in view of the quadrant glitches existence produced by the friction force. In addition, further study is required on PID controller with three nonlinear components in order to produce better tracking machine tool performance.